A critical evaluation of grid stability and codes, energy storage and smart loads in power systems with wind generation. (15th August 2020) - Al kez, Dlzar; Foley, Aoife M.; McIlwaine, Neil; Morrow, D. John; Hayes, Barry P.; Zehir, M. Alparslan; Mehigan, Laura; Papari, Behnaz; Edrington, Chris S.; Baran, Mesut
Abstract: Existing power systems are facing new challenges in maintaining the security of the power system as the penetration of variable renewable energy technologies, such as variable speed wind turbines, increase. System non-synchronous generation replaces conventional generators as penetration of renewable generation increases. This affects system rotational inertia and limits the number of online thermal generators that can provide frequency stability services and system-wide areas voltage stability. This evolution has resulted in some changes to existing grid codes and new ancillary services. Furthermore, it could provide opportunities to address the security of the system utilizing modern smart technologies, e.g. smart loads, heat pumps and electric vehicles. The aim of this paper is to evaluate the impacts of large-scale renewable power generation on power system dynamics from the perspective of the power system operator. It focuses on the grid codes implications and challenges specifically. Synthetic inertia response opportunities from smart loads, electric vehicles and energy storage technologies and dispatching wind farms during frequency excursions are analyzed and thoroughly discussed. The key finding is that rethinking in the development of grid code requirements and market mechanisms are needed if a power system based on 100% power electronic renewable generation is to be achieved. This type of power system would need a range of technologies to provide the types of ancillary (i.e. system) services required, as none of the technologies alone can tackle all the challenges presented. Highlights: First thorough study of impact of converter-based renewable generation on grid system dynamics. Crucial for energy storage and smart appliances to respond in less than 500 ms to reduce trip risk. Anti-islanding RoCoF relays should be set for 0.5 Hz/s for a window of 500 ms Frequency limitations in renewable dominant countries are typically between 49.8 Hz and 50.2 Hz. New fast frequency services to large disturbances are within 500 ms to 2.0 s from an event start.